Evaluation of Anticonvulsant Activity of Zinc in Albino Rats - Sharanabasayyaswamy B Hiremath and Mohammad Ameeruddin Kamdod (Journal of Applied Pharmaceutical Science)
Mechanism of action of both magnesium and zinc in mediating their antidepressant activities is supposed to be through NMDA receptor antagonism. In the background of similarity in mechanism of action of zinc and magnesium as antidepressant through antagonism of NMDA receptors and evidences for anticonvulsant actions of magnesium being mediated through NMDA receptors blockade; present study was designed to test whether zinc has an additional anticonvulsant activity. Thirty six albino rats of either sex were divided in to 6 groups with 6 animals in each group. Group-I received distilled water (1ml/kg body weight) was control group. Group-II receiving phenytoin sodium (20mg/kg body weight) was the standard group. Group-III, IV and V were test groups receiving zinc sulfate at doses of 30mg/kg, 150mg/kg and 300mg/kg respectively. Animals were screened for anticonvulsant activity by Maximum Electroshock (MES) method and for generalized CNS depressant effect by photo-actometer method. With regard to anticonvulsant activity there was no statistically significant differences between any of the zinc sulfate treated groups with control and standard drug phenytoin. There was no evidence for possible anticonvulsant activity of zinc after single dose treatment at three selected doses in presence of generalized CNS depressant effect.
Keywords: Zinc sulfate, Maximum Electro-shock method, Photo-actometer.